2009
DOI: 10.1007/s00705-009-0338-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of adenoviral infections in Cuba: report of an unusual association of species D adenoviruses with different clinical syndromes

Abstract: Adenoviruses are common pathogens that are responsible for a wide variety of infectious syndromes. The objectives of this study were to identify and characterize members of different adenovirus species at the molecular level and to describe the correlation between viruses and clinical syndromes during a period of 4 years. Between 2002 and 2006, 45 of 512 respiratory specimens (8%) from patients with acute respiratory tract infection tested positive for adenovirus. Four adenovirus isolates from samples sent for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
1
8
0
2
Order By: Relevance
“…Meningitis by HAdV has been identified as a complication of pneumonia as a result of disseminated infection in immunocompromised patients; the infection rarely presents primarily as a CNS disease [Studahl et al, 1998]. HAdV‐5, identified in this study as the cause of one case of cerebellitis with a history of conjunctivitis, and another of meningitis, is usually recognized as a major cause of respiratory infection in infants (bronchiolitis) [Belsy et al, 2009].…”
Section: Discussionmentioning
confidence: 94%
“…Meningitis by HAdV has been identified as a complication of pneumonia as a result of disseminated infection in immunocompromised patients; the infection rarely presents primarily as a CNS disease [Studahl et al, 1998]. HAdV‐5, identified in this study as the cause of one case of cerebellitis with a history of conjunctivitis, and another of meningitis, is usually recognized as a major cause of respiratory infection in infants (bronchiolitis) [Belsy et al, 2009].…”
Section: Discussionmentioning
confidence: 94%
“…While Ad has been known to be occasionally associated with acute bronchiolitis, the role of serotype 2 has not been previously reported. One study from Cuba reported that serotype 5 accounted for 71 % of the 14 cases of acute bronchiolitis identified, but serotype 2 was not tested for in that study [2]. Their sample size was smaller (49 cases) and with a lower serotyping rate (63 %).…”
Section: Discussionmentioning
confidence: 96%
“…Son yıllarda yapılan çalışmalarda ise, AFP'li olguların dışkı ve diğer klinik örneklerinde bazı adenovirus tiplerinin saptanması, bu virusların AFP etiyolojisindeki olası rollerini düşündürmeye başlamıştır [8][9][10][11][12][13] . Bu noktadan hareketle, bu çalışmada, AFP şüpheli olguların dışkı örneklerinden adenovirus izolasyon sıklığının araştırılması amaçlanmıştır.…”
Section: Introductionunclassified